Perancangan Sistem Perpustakaan Berbasis Web Di Smp Negeri 18 Medan - Silvia; Suheri; Hendry (CV. Hawari, 2026)
School libraries play an important role in supporting learning activities and improving students’ literacy. However, library management in many junior high schools is still carried out manually, causing various problems such as difficulties in searching book data, high risk of recording errors in borrowing and returning transactions, and delays in report generation. This study aims to design and implement a web-based library system to improve the efficiency of library management at SMP Negeri 18 Medan. The research method used is the System Development Life Cycle (SDLC) with the Waterfall model, which consists of problem identification, data collection, requirements analysis, system design, implementation, and system testing. Data were collected through observation, interviews, and literature study. The results show that the developed web-based library system is able to manage book collections, member data, and borrowing and returning transactions in an integrated and accurate manner. In addition, the system facilitates report generation and improves access to library information for students and teachers. Therefore, the proposed system is considered an effective solution for enhancing the quality of school library services and supporting the utilization of information technology in the educational sector.